2014
DOI: 10.1155/2014/418180
|View full text |Cite
|
Sign up to set email alerts
|

Transient Global Amnesia Associated with an Acute Infarction at the Cingulate Gyrus

Abstract: Background. Transient global amnesia (TGA) is a syndrome of sudden, unexplained isolated short-term memory loss. In the majority of TGA cases, no causes can be identified and neuroimaging, CSF studies and EEG are usually normal. We present a patient with TGA associated with a small acute infarct at the cingulate gyrus. Case Report. The patient, a 62 year-old man, developed two episodes of TGA. He had hypertension and hypercholesterolemia. He was found to have an acute ischemic stroke of small size (15 mm of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Forster et al in Germany looked at 386 patients diagnosed with TGA at their hospital, and, of the 27 patients who received MRI evaluation, all 12 with DWI lesions were in the hippocampus [4]. Furthermore, it was noted that the properties of these lesions compared to those of pure hippocampal strokes were indistinguishable in terms of DWI and apparent diffusion coefficient (ADC) [6], which seems to suggest that these are true infarctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forster et al in Germany looked at 386 patients diagnosed with TGA at their hospital, and, of the 27 patients who received MRI evaluation, all 12 with DWI lesions were in the hippocampus [4]. Furthermore, it was noted that the properties of these lesions compared to those of pure hippocampal strokes were indistinguishable in terms of DWI and apparent diffusion coefficient (ADC) [6], which seems to suggest that these are true infarctions.…”
Section: Discussionmentioning
confidence: 99%
“…Lesion sizes varied between 3 and 6 mm. Comparatively, patients with pure hippocampal strokes could have no memory involvement whatsoever [6]. Thus, the fact that neither the presence, nor the location, nor the size of DWI hyperintensities can consistently correlate with the severity of TGA findings only highlights how lacking the current literature is in understanding the significance of these ischemic-like lesions in the pathogenesis of TGA.…”
Section: Discussionmentioning
confidence: 99%
“…In accord with the hypothesized etiology of venous overflow, our findings replicate other studies showing reversible ischemia in hippocampal regions associated with this syndrome. Interestingly, lesions to other structures known to be involved in declarative memory (e.g., thalamus, cingulate gyrus, and basal ganglia) have been associated with TGA [ 6 ]. In addition to being rare because of their bilateral nature, the lessions shown here are unique in that very few authors have reported such changes in the acute phase of TGA.…”
Section: Discussionmentioning
confidence: 99%
“…However, some recent evidence suggests that structural abnormalities are associated with TGA. Several cases have been reported, which suggest that brain structural abnormalities such as acute infarction of the cingulate gyrus and fornix may induce TGA (Gallardo‐Tur, Romero‐Godoy, de la Cruz Cosme, & Arboix, ; Gupta, Kantor, Tung, Zhang, & Albers, ). Recently, studies using diffusion‐weighted imaging MRI have consistently revealed that the acute stage of TGA is associated with precise focal lesions in hippocampal CA1 (Bartsch et al., ; Kim et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…TGA. Several cases have been reported, which suggest that brain structural abnormalities such as acute infarction of the cingulate gyrus and fornix may induce TGA (Gallardo-Tur, Romero-Godoy, de la Cruz Cosme, & Arboix, 2014;Gupta, Kantor, Tung, Zhang, & Albers, 2014).…”
Section: Introductionmentioning
confidence: 99%